Soil and Water Conservation : Challenges and Opportunities/ (Acc: 1616) challenges and opportunities - Bhushan, L. S.; Abrol, I. P.; Rama Mohan Rao, M. S.; Indian Association of Soil & Water Conservationists (Dehradun : Indian Association of Soil and Water Conservationists, 1998)
Conference held in New Delhi on Dec. 4-8, 1994, and organized by the Indian Association of Soil and Water Conserevationists.
Keywords: Challenges and Opportunities; Water conservation